Reflections on the Use of Ecological Attributes and Traits in Quaternary Botany - Birks, H. John B. (Frontiers in Ecology and Evolution, 2020)
There has been an upsurge of interest and research activity in trait-based approaches in ecology, biogeography, and macroecology. I discuss if this upsurge has impacted Quaternary botany (the study of plant remains preserved in sediments). I show that ecological attributes (including traits) have played and continue to play an integral part in the interpretation of Quaternary botanical data in terms of reconstructing past environments and interpreting long-term changes in plant assemblages. This use started over 120 years ago and continues to the present. It is unclear if a ‘new’ Quaternary botany based on traits will develop because of the taxonomic limitations of much Quaternary botanical data.